Analisis Penggunaan Dana Bantuan Operasional Sekolah dalam Meningkatkan Kompetensi Profesional Guru (Studi Kasus Penggunaan Anggaran di SMP Negeri 36 Kota Bandung) - H. Soro, Suharyanto; Rifandi, Ahmad; Sofayantina, Yanti; Listianti, Listianti (LP. Ma'arif Janggan Magetan, 2024)
The quality of education is realized through one of the financing management. Management in this context refers to the identification, planning, implementation, and evaluation of educational units. Financing through School Operational Assistance (BOS) funds is considered not to have been realized according to expectations, namely that the financing has not been able to improve the professional competence of teachers. This study aims to find and describe the use of school operational funds in improving the professional competence of teachers. The researcher used a case study approach with a qualitative research paradigm. The research data collection method used observation, interview, and documentation study methods. The researcher took samples using purposive sampling. The research location was at SMP 36, Bandung City. The research activity was carried out in the 2024 academic year. The results of the study showed that (1) SMPN 36, Bandung City had carried out mature budget planning in order to improve the professional competence of teachers; (2) Planning emphasizes transparency in budget management, budget realization that is relevant to the RKAS, active participation of all stakeholders and the quality of school facilities and infrastructure; (3) The effectiveness of the use of the school budget plays a significant role in supporting the improvement of the professional competence of teachers (learning facilities, teacher training, and student support programs). In other words, good, transparent and targeted budget (and BOS) realization has a positive impact on improving teachers' professional competence.